Transforming Text: Finding the Poem Within - Deborah F. Carrington; Chapman Hood Frazier (Journal of the Assembly for Expanded Perspectives on Learning, 2010)
This essay illustrates creative ways for students to re-envision a page of text in order to discover multiple meanings through the integration of visual art and poetry.